2019
DOI: 10.1111/apm.12971
|View full text |Cite
|
Sign up to set email alerts
|

Serum TLR2 and TLR4 levels in colorectal cancer and their association with systemic inflammatory markers, tumor characteristics, and disease outcome

Abstract: Paarnio K, Tuomisto A, V€ ayrynen SA, V€ ayrynen JP, Klintrup K, Ohtonen P, M€ akinen MJ, M€ akel€ a J, Karttunen TJ. Serum TLR2 and TLR4 levels in colorectal cancer and their association with systemic inflammatory markers, tumor characteristics, and disease outcome. APMIS 2019; 127: 561-569.Toll-like receptors (TLRs) are involved in colorectal cancer (CRC) pathogenesis. However, the significance of serum TLR concentrations in CRC is unknown. We analyzed serum TLR2 and TLR4 concentrations with ELISA in preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…TLR 1, 2, 5, 6, and 10 are extracellular TLRs, whereas TLR3, 7, 8, and 9 are localized in intracellular organelles (12). TLR2 and TLR4 are two major TLRs that have been widely investigated for their involvement in inflammatory responses and cancers (13). The expression and clinical significance of TLR4 have been reported in patients with BCa (14).…”
Section: Introductionmentioning
confidence: 99%
“…TLR 1, 2, 5, 6, and 10 are extracellular TLRs, whereas TLR3, 7, 8, and 9 are localized in intracellular organelles (12). TLR2 and TLR4 are two major TLRs that have been widely investigated for their involvement in inflammatory responses and cancers (13). The expression and clinical significance of TLR4 have been reported in patients with BCa (14).…”
Section: Introductionmentioning
confidence: 99%
“…One of the core enriched genes of the present analysis was the co-chaperon HSP90B1, which directly influences the functionality of most TLRs (Graustein 2018). Recently, it was demonstrated that TLR2 was highly upregulated in CRC compared to normal mucosa (Paarnio et al 2019) and TLRs might even prove to be important as diagnostic markers. Furthermore, TLRs correlate with high inflammation and poor prognosis in CRC patients (Paarnio et al 2017).…”
Section: Hep Vs M0: Reactome Toll-like Receptor-cascadementioning
confidence: 79%
“…Among many malignancies including CRC, local and systemic inflammation has been studied separately, with very few studies assessing the association between local inflammation and SIR. Paarnio et al [13] studied both the serum and tumoral expression of TLR2 and TLR4 finding no association with each other, although patients with detectable serum TLR2 levels exhibited higher TLR2 immunoexpression in the normal colorectal mucosa. They found that patients with undetectable TLR2 serum levels had higher CRP values, indicative of some connection between local and systemic inflammation [13].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this was the first study to describe the role of TLR5 in CRC. In addition, a low serum TLR2 associated with a high serum C-reactive protein (CRP) in another published study [13].…”
Section: Introductionmentioning
confidence: 99%